Burnout Syndrome among Doctors of a Tertiary Care Hospital in Southern Kerala. (Indian Journal of Public Health Research & Development, 2025)
Background: Burnout in health care professionals has gathered significant attention due to its impact  on quality of care and medical personnel . As a result of the intense emotional demands of the work environment, clinicians are particularly susceptible to develop burnout above and beyond usual workplace stress. In order to cultivate occupational intervention programs there is a need to estimate the prevalence of burnout among physicians.  Methods: From a total of 108 participants, data was collected using a questionnaire primarily consisting of “personal burnout” domain of the Maslach Burnout Inventory, which is a validated instrument to assess the burnout using three dimensions which includes emotional exhaustion, depersonalization and low personal accomplishment. In addition to summary statistics, analysis was done to find out the factors significantly affecting burnout. Result and conclusion: The findings of this study indicate that the burnout syndrome is present among doctors across all specialty categories.3.7% showed high emotional exhaustion,13.9 showed high depersonalization and 12% showed low personal accomplishment. Age, gender, working hours, years of experience were the some of the factors significantly affecting burnout. Burnout exists among healthcare professionals and measures should be taken to identify causes and take remedial actions.
Keywords: Burnout, Healthcare Professionals, Kerala, Maslach Burnout Inventory.